Influence of Housing and Management on Claw Health in Swiss Dairy Goats - Lisa Marie Sailer; Mirjam Holinger; Joan-Bryce Burla; Beat Wechsler; Patrik Zanolari; Katharina Friedli (Animals, 2021)
Due to a rising demand for goat milk and goat milk products worldwide, it is likely that dairy goat production will be intensified in the future, with larger herds per farm. In Switzerland, as in many other countries with intensive farming systems, dairy goats are typically housed on deep litter, with little access to hard abrasive surfaces. Such housing conditions will result in wall horn overgrowth. The aim of this study was to gain profound knowledge on the occurrence of overgrown wall horn, its impact on claw health and locomotor behavior, and possible adverse effects on animal welfare. Additionally, housing and management factors that may contribute to non-physiological claw conditions were evaluated. To compare claw conditions after the summer grazing period and the winter indoor housing period, data were collected on 28 Swiss dairy goat farms in autumn and spring (621 goats in total). Claw lesions were recorded with the help of a “claw card” documenting each claw. Furthermore, pictures were taken of each claw to determine the severity of wall horn overgrowth. Locomotion behavior (activity, lying time and lying bouts) was recorded with three-dimensional accelerometers fixed to the goats’ hind legs. In autumn, 66.7% of the examined claws showed moderate overgrowth, 32.4% severe overgrowth and 0.9% no overgrowth. In spring, 47.4% of the examined claws were affected with moderate overgrowth, 52.6% with severe overgrowth and 0.0% with no overgrowth. Horn separation (48.1% of examined claws) and sole hemorrhages (16.0% of examined claws) were the most frequent lesions. In goats with severely overgrown claws, the risk of developing sole hemorrhages was doubled compared with moderate overgrowth. The occurrence rate of horn separation was lower if the trimmer had attended a special skills training course (p < 0.001). Furthermore, locomotor activity (p < 0.01) and the number of lying bouts per day (p < 0.01) were higher in spring than autumn. Neither the goats’ activity nor the number of lying bouts per day differed before and after claw trimming. Finally, season and trimming were not associated with the goats’ total lying time. A certain extent of wall horn overgrowth in dairy goat claws cannot be avoided under the housing conditions typical for Swiss farms. Severe wall horn overgrowth is associated with an increase in the proportion of claws with sole hemorrhages. Therefore, regular and careful functional claw trimming, taking the housing situation (deep bedding, access to pasture, grazing on alpine pasture) into account, should be promoted.